1/4(x-3) + 5/6(2x+7) = -2/3(3x-1) - 4/5(5x+2)
(1/4)(x-3) + (5/6)(2x+7) = -(2/3)(3x-1) - (4/5)(5x+2)
x/4 - 3/4 + 10x/6 + 35/6 = -6x/6 + 2/3 - 20x/5 - 8/5
x/4 - 3/4 + 5x/3 + 35/6 = -x + 2/3 - 4x - 8/5
group number of the same term
x/4 + 5x/3 + x + 4x = 2/3 - 8/5 + 3/4 - 35/6
make the denamenator of left side equal
x(3)/4(3) + 5x(4)/3(4) = 2/3 - 8/5 + 3/4 - 35/6
3x/12 + 20x /12 = 2/3 - 8/5 + 3/4 - 35/6
Make the denamenator of the right side equal
3x/12 + 20x /12 = 2(20)/3(20) - 8(12)/5(12) + 3(15)/4(15) - 35(10)/6(10)
3x/12 + 20x /12 =40/60 - 96/60 + 45/60 - 350/60
now we can add the numerator
23x/12 = - 361/60
23x = 12 (- 361/60)
x = (12/23)(- 361/60)
x = - 361 /115